POLITIK HUKUM MAHKAMAH KONSTITUSI DALAM JUDICIAL REVIEW (SEBUAH PENDEKATAN SOSIOLOGIS) - Murdoko, Murdoko (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2020)
AbstractThe collapse of the New Order and the subsequent rise of the Reformation changed the political system, the legal system and the economic system. The political system and legal system almost all agree to change to become more liberal by promoting human rights, but for the economy there is division, which is to change to become liberal as in politics and law, and remain "integralistic" or family that leads to socialism. As a result, the Constitutional Court whose duty is to maintain the interpretation of the constitution by law allows for several models of decisions, namely the legal, attitude, strategic and institutional models.Keywords: Reformation, family, Liberal, legal model, attitude model, strategic model, and institutional model.Â AbstrakRuntuhnya Orde Baru dan diikuti munculnya Reformasi telah merubah sistem politik, sistem hukum, dan sistem ekonomi. Sistem politik dan sistem hukum hampir seluruhnya menyetujui berubah menjadi lebih liberal dengan mengedepankan HAM, tetapi untuk ekonomi terjadi pembelahan, yaitu ikut berubah menjadi liberal sebagaimana dalam politik dan hukum, serta tetap â€œintegralistikâ€ atau kekeluargaan yang mengarah pada sosialisme. Akibatnya terhadap Mahkamah Konstitusi yang bertugas untuk menjaga interpretasi terhadap konstitusi oleh undang-undang memungkinkan terjadinya beberapa model putusan, yaitu model legal, sikap, strategis, dan institusional.